The relationship between students' perception to the learning media, digital literacy skills, and self-regulated learning with students' learning outcomes in the rural area - Arsad Bahri; Wahyu Hidayat M; Kurnia Prima Putra; Nur Aisyah Ainun; Nurheni Arifin (OmniaScience, 2024)
This study aims to determine the relationship between students' perception to the learning media, digital literacy skills, and self-regulated learning with students' cognitive learning outcomes in the rural area. This study was the ex post facto with quantitative data. The method used was differential causal comparative with multiple linear regression analysis. The three variables were measured using a questionnaire, cognitive learning outcomes was measured by test. The results showed that students' perception to the learning media, digital literacy skills, and self-regulated learning on students' cognitive learning outcomes had a moderate simultaneous relationship. The findings also showed that the contribution of self-regulated leraning to the cognitive learning outcomes was the higher (71.42%). The contribution of the three variables to cognitive learning outcomes was 86.41%. Based on related facts, research recommendations can be expanded by measuring from several other rural areas and examining several other variables, especially those that support the learning process oriented towards empowering 21st century competencies by utilizing the latest technological developments and that can reach all regions of Indonesia, especially in rural areas so as to minimize the gap in the quality of education in Indonesia.